Exploring Sharia-Compliant Monetary Policy: Implications for Economic Stability and Education in Islamic Economics - Azulaidin; Anwar; Tajhizi, Azra (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study examines Islamic monetary policy from the perspective of Islamic economic education, focusing on its implications for economic stability, wealth distribution, and the prohibition of interest (riba). The central aim of this research is to explore how Sharia-compliant monetary policies, which emphasize justice, equity, and the use of profit-sharing instruments such as mudarabah, musyarakah, and ijarah, can contribute to reducing inequality and fostering long-term economic growth. A qualitative approach was adopted, using a systematic literature review to analyze the impact of these policies within Islamic economic education. The literature review encompassed articles published between 2019 and 2024, with a particular focus on studies that discuss the application of Sharia-compliant financial instruments in various global contexts. The findings reveal that Sharia-compliant monetary policies have the potential to stabilize economies by ensuring fair distribution of wealth, promoting social justice, and offering an alternative to the interest-based financial systems that dominate conventional economies. However, challenges remain in the broader adoption of these systems due to the lack of infrastructure and the resistance of conventional financial institutions. This study contributes to the existing literature by providing insights into the integration of Islamic monetary policy into modern economic education and offering a comprehensive review of the principles, strengths, and challenges of Sharia-compliant financial systems.